İl,.AHiYAT FAKÜLTESi ÖGRENCiLERiNiN ARAPÇA ÖGRENMEDEKi MOTiVASYON DÜZEYLERi (Fırat Ün. ilahiyat Fak. Örneği) - Deliçay, Tahsin (Fırat University, 2005)
In Turkey tlıere are so me dijfıculties of Arabic teac/ı ing, both for students and instnıctors. The lack of motivation in Arabic teaching, as it was the case in every subject, is one of the main problems. In this ar/icle, the reasons of the lack of motivation together ıvith other teaming dijfıculties, is assessed by using questionnaires. Based on the results of the questiomıaires, some obsen,ations and remedies are put fonvard.
Keywords: Religious Studies; Din Araştırmaları